(untitled) (Bangladesh Journal of Agriculture, 2025)
The research was conducted at Germplasm Centre of Agrotechnology Discipline, Khulna University, Khulna during the period from November 2021 to April 2022, to evaluate the growth and yield performance of selected six sweet potato varieties. The experiment consisted of six sweet potato varieties: BARI misti alu10, BARI misti alu11, BARI misti alu12, BARI misti alu14, BARI misti alu15 and local variety (check). The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. The parameters measured included number of sprouts, plant height, number of branches, branch length, number of leaves, length of leaves, breadth of leaves, number of tubers, weight of tubers and yield (t ha-1). The results of the study revealed that, BARI misti alu10 showed maximum yield (54.33 t ha-1) followed by BARI misti alu14 (44.66 t ha-1). Based on the findings of the experiment, BARI misti alu10 and BARI misti alu14 was found better in respect yield and yield contributing characters. The outcome of this study could be helpful in germplasm management, hybridization programs and crop improvement program. Bangladesh J. Agri. 2024, 49(2): 45-52